PENGARUH TESTIMONI, ENDORSEMENT DAN TAMPILAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU COMPASS PADA MEDIA SOSIAL INSTAGRAM DI KOTA BANJARMASIN - Hernando Rekyantiosani; Setio Utomo; Noor Hidayati; Maryono (Smart Business Journal (SBJ), 2023)
This study aims to examine the partial and simultaneous effect of Testimonials, Endorsements and Product Displays on Purchase Decisions by Consumers of Compass Shoes in Banjarmasin City. The research approach used is a quantitative approach, the sample taken is 75 respondents with purposive sampling technique, data collection using questionnaires, while the results of data analysis using multiple linear regression. The results of this study prove that Testimonials (X1) have a partially significant effect on Purchase Decisions with a large influence of 0.261 or 26.1%, Endorsements (X2) have a partially significant effect on Purchase Decisions 0.383 or 38.3% and Product Display (X3) has a significant effect. partially to the Purchase Decision 0.112 or 11.2%. Testimonials, Endorsements and Product Displays simultaneously have a significant effect on Purchase Decisions with a large effect of 0.756 or 75.6%.